Energy conversion efficiency improvement of ZnO dye-sensitized solar cells by dye re-adsorption and N-P junction technique - Surat Futemvong (2018)
In this work, ZnO Dye-sensitized solar cells (DSSCs) with dye re-adsorption technique and NiO thin films coated as n-p junction were investigated. The general structures of ZnO DSSCs were FTO/ZnO as a photo-electrode, Eosin-Y as a dye sensitizer, iodine/iodide solution as an electrolyte and Pt/FTO as a counter-electrode. For dye re-adsorption technique, ZnO photo-electrodes were soaked into Eosin-Y solutions as dye adsorption, then soaked into ethanol as dye desorption (3-step sequence). From the absorption spectra, the absorbance values depended on the dye re-adsorption steps suggesting the removal of the excess dye molecules during the process. For n-p junction, NiO thin films were coated on ZnO with 0.6 mg to form a barrier layer in photo-electrode called ZnO/NiO. The optimum conditions for the dye re-adsorption technique were selected with n-p junction DSSCs. The DSSCs were investigated by using J-V measurement and electrochemical impedance spectroscopy. It was found that ZnO and ZnO/NiO DSSCs with first dye re-adsorption exhibited the highest energy conversion efficiency of 0.99% and 1.10%, respectively. The improvement of energy conversion efficiency due to dye re-adsorption and n-p junction can be explained in terms of reduction of dye aggregation and decrease of charge recombination in photo-electrode.